Complications After Thyroidectomy in Children: Lymph Node Dissection Is a Risk Factor for Permanent Hypocalcemia - van Rooijen, Jesse J.; van Trotsenburg, A. S. Paul; van de Berg, Daniël J.; Zwaveling-Soonawala, Nitash; Nieveen van Dijkum, Els J. M.; Engelsman, Anton F.; Derikx, Joep P. M.; Mooij, Christiaan F. (Frontiers in Endocrinology, 2021)
Background: Thyroidectomy is a treatment option in some benign thyroid disorders and the definitive treatment option for thyroid cancer. As postoperative mortality is extremely rare data on postoperative complications and long-term health consequences are important. Objective: To evaluate the frequencies of short- and long-term complications, and their risk factors in pediatric patients (0-18 years) who underwent a thyroidectomy in a tertiary children’s hospital. Methods: A retrospective single center study was performed including all pediatric patients who underwent a thyroidectomy between January 2013 and February 2020. Results: Forty-eight patients were included in this study (mean age 14.6 years). Twenty-nine total thyroidectomies and 19 hemithyroidectomies were conducted. Thyroid carcinoma was the indication to perform a thyroidectomy in 12 patients, 36 patients underwent a thyroidectomy because of a benign thyroid disorder. Postoperative hypocalcemia was evaluated in patients who underwent a total thyroidectomy. Rapidly resolved hypocalcemia was observed in three patients (10.3%), transient hypocalcemia in 10 patients (34.5%) and permanent hypocalcemia in six patients (20.7%). Permanent hypocalcemia was only seen in patients who underwent a thyroidectomy combined with additional lymph node dissection because of thyroid carcinoma (thyroid carcinoma: OR 43.73, 95% CI [2.11-904.95]; lymph node dissection: OR 76.14, 95% CI [3.49-458.98]). Transient and permanent recurrent laryngeal nerve injury was reported in four (8.3%) and one (2.1%) of all patients, respectively. Conclusion: Permanent postoperative complications after thyroidectomy are rare in pediatric patients undergoing a thyroidectomy without lymph node dissection. However, in this age group permanent hypocalcemia occurs more frequently after thyroidectomy with additional lymph node dissection because of thyroid cancer. With respect to quality of life, especially of pediatric thyroid cancer patients, reducing this complication is an important goal.